Safety awareness in construction industry (a case study at Shah Alam) / Ahmad Ab. Majid - Ab. Majid, Ahmad (2010)
The construction industry is known as one of the most hazardous activities. Safety is an important aspect with respect to the overall task in construction industry. Recently the issues of safety have attracted the attention of many parties in the construction industry in Malaysia. The construction sites have been highlight as one of the highest number of accidents compare to the other industry. One of the main causes of accidents on construction sites are the low awareness of the safety. This study is carried out to examine the level of safety awareness among the workers on construction sites. This study also carried out to examine the implementations of safety awareness among management team. Other than that, the aim of this study is to recommend improving measures of safety on construction sites. A total of 45 sets of questionnaires have been distributed to the workers and management an J the data were analyzed by using average index method. The analysis result shows the level of safety awareness among the workers on construction sites is high. Several safety measures were implemented by management to show that management aware and concern about the safety at the construction sites including safety equipment, safety plan, site visitors and machinery and equipment. Further improvement that can be implemented include tool box meeting, giving more training to the workers, safety inspection every week, conduct a regular site safety meeting and take the strictly action to the workers who are not follow the safety rules.